Modelling of acoustic ageing of rubberized pavements. (March 2019) - Licitra, Gaetano; Moro, Antonino; Teti, Luca; Del Pizzo, Alessandro; Bianco, Francesco
Abstract: Tyre-road noise is the most important source of traffic noise in the mid-to-high speed range. The use of low noise road surfaces represents an ideal solution to mitigate traffic noise, because it directly affects the source, generating a widespread benefit for all the dwellings near the road and decreasing the number of people annoyed. More knowledge about long-term acoustic performance is required to promote the use of low noise road surfaces as mitigation action. In fact, as for a traditional road surface, the acoustic properties of low noise surfaces worsen over time: only by knowing the initial noise reduction and its time evolution, public administrations can design their application and related maintenance plans. In this work, an innovative approach was used to investigate and model acoustic ageing of some rubberized road surfaces surveyed for several years. This type of quiet pavements represents an efficient road surface technology in terms of traffic noise reduction. A new regression model was applied to estimate the acoustic ageing of the investigated pavements, considering the complex interacting system composed of three main elements: pavement type, traffic loads and climatic conditions.